Cross- and axial-peak intensities in 2D-SLF experiments based on cross-polarization - the role of the initial density matrix - Das, Bibhuti B.; Ajithkumar, Thalasseril G.; Sinha, Neeraj; Opella, Stanley J.; Ramanathan, K. V. (Journal of Magnetic Resonance, 2007)
Simulations and experiments on simple oriented systems have been used to estimate the relative ratio of cross-peak to axial-peak intensities in 2D-SLF experiments based on dipolar oscillations during cross-polarization (CP). The density matrix prior to dipolar evolution is considered and for an isolated spin pair, it is shown that direct calculations of the ratios match well with simulations and experimental results. Along with the standard CP pulse sequence, two other pulse sequences namely CP with polarization inversion (PI-CP) and another novel variation of the standard CP experiment (EXE-CP) reported recently have been considered. Inclusion of homonuclear dipolar coupling has been observed to increase the axial-peak intensities. In combination with Lee-Goldburg (LG) decoupling, experiments on an oriented liquid crystalline sample have been carried out and the performance of the pulse schemes have been compared. The applicability of the new pulse sequence for different samples and different nuclei is discussed. Such studies are expected to lead to a better understanding of the experiments and to the design of useful pulse sequences. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: cross polarization; oriented molecules; PISEMA; SLF

Improved pulse schemes for separated local field spectroscopy for static and spinning samples - Das, Bibhuti B.; Ajithkumar, Thalasseril G.; Ramanathan, K. V. (Solid State Nuclear Magnetic Resonance, 2008)
An improved pulse sequence for SLF experiments based on the magic sandwich (MS) scheme for homonuclear dipolar decoupling is proposed. The sequence incorporates a double MS, both on I and S spins and has been named as EXE-MS2. The proposed scheme which has a scaling factor of 1 is observed to be free from low intensity artifacts and provides better line-widths particularly for S spins labeled at multiple sites. The pulse sequence which has been applied on static oriented samples incorporates the EXE scheme where direct polarization of the S spin in the B-0 field is utilized in the place of polarization inversion and is observed to perform well without any loss of sensitivity while ensuring considerable reduction in rf power input into the sample. The EXE scheme has also been tested for solid samples under MAS. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: magic sandwich pulses; PISEMA; SLF